Exceptional cyclability of thermally stable PVdF-co-HFP/SiO2 nanocomposite polymer electrolytes for sodium ion batteries - Das, Akhila; Melepurakkal, Amrutha; Sreeram, Pranav; Gireesh, K. T.; Balakrishnan, Neethu T. M.; Fatima, M. J. Jabeen; Pullanchiyodan, Abhilash; Ahn, Jou-Hyeon; V. Shelke, Manjusha; Raghavan, Prasanth (Journal of Energy Storage, 2023)
Thermally stable composite polymer electrolyte (CPE) devising PVdF-co-HFP polymer with in-situ generated silica (SiO2) as filler is synthesised via non-solvent- induced phase inversion technique. The filler loading of in-situ synthesised silica in PVdF-co-HFP is varied from 0 to 9 wt% and its morphological, thermal and electrochemical characterization is carried out. Among the different composite electrolytes, the PVdF-co-HFP containing 6 wt% SiO2 shows the uniform microporous structure with a highest porosity (84 %), surface area (784.14 m(2) g(-1)), electrolyte uptake (262 %) and electrolyte retention value (0.48). The incorporation of in-situ SiO2 on CPE shows not only the enhancement in thermal stability but also reduced thermal shrinkage with an increase in the filler content. The electrochemical studies of PVdF-co-HFP containing 6 wt% SiO2 shows a higher ionic conductivity (0.71 mS cm(-1)) and potential stability >4.5 V verses Na/Na+. The Na-ion half-cells assembled with PVdF-co-HFP/SiO2 composite electrolyte show a specific capacity of similar to 120 mAh g(-1) at 0.3C rate in room temperature and a stable cycle performance with a Coulombic efficiency of around 100 % for 200 cycles.
Keywords: Composite electrolytes; Coulombic efficiency; polymer electrolytes; Sodium ion batteries; specific capacity; thermal stability

Safety enhanced novel polymer electrolytes for lithium-ion battery: Anomalous output performance with long term cycling stability by doping and polymer blending - Balakrishnan, Neethu T. M.; Melepurakkal, Amrutha; Das, Akhila; Kenz, K. T. Mohammed; Subramaniam, Mohanapriya; Shelke, Manjusha; Pullanchiyodan, Abhilash; Raghavan, Prasanth (MATERIALS TODAY CHEMISTRY, 2024)
Keywords: Blend polymers; Ceramic fillers; Gel polymer electrolytes